Converts of conviction faith and scepticism in nineteenth century European Jewish society - Ruderman, David B. (Studies and texts in scepticism, 2018)
The approach of the authors of this book is to avoid broad generalizations about the modern convert in favor of detailed case studies of specific converts in four distinct localities: Germany, Russia, Poland, and England, all living in the nineteenth- century. In so doing, it underscores the individuality of each convert's life experience and self-reflection and the need to examine more intensely this relatively neglected dimension of Jewish and Christian cultural and intellectual history